An authenticated self-healing key distribution scheme based on bilinear pairings - Tian, Biming; Chang, Elizabeth; Hussain, Farookh Khadeer; Dillon, Tharam S.; Han, Song (IEEE, 2009)
Self-healing key distribution mechanism can be utilized for distributing session keys over an unreliable network.A self-healing key distribution scheme using bilinear pairings is proposed in this paper. As far as we know, it is the first pairingbased authenticated self-healing key distribution scheme. The scheme achieves a number of excellent properties. Firstly, the users can check the integrity and correctness of the ciphertext before carrying out more complex key recovery operations thus fruitless work can be avoided. Secondly, the scheme is collusion-free for any coalition of non-authorized users. Thirdly, the private key has nothing to do with the number of revoked users and can be reused as long as it is not disclosed. Finally, the storage overhead for each user is a constant.